2019
DOI: 10.21608/jsrs.2019.77052
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabutylphosphonium-salicyl-imine-chitosan metallo-Schiff bases:Supramolecular architectures as multifunctional pharmacological materials.

Abstract: Introduction Chitosan (CS) is one of the most readily available biopolymer due to preparing it from alkaline N-deacetylation of Chitin, which is the most plentiful polysaccharide in nature. The structure of chitosan is a linear co-biopolymer of 2-acetamido-2-deoxy-β-Dglucopyranose(GluNHAc) with2-amino-2-deoxy-β-D-glycopyranose (GluNH 2) (Rinaudo, M., 2006).Due to the unique properties of chitosan such as a biocompatibility, biodegradability and also its antimicrobial and anti-cancer activity (Choi et al., 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…NMR observations in DMSO-d 6 as solvent: The 1 H-NMR spectrum of un-complexed ligand (H 2 L) noticed highly de-shielded singlet at a low-field region δ = 8.66 ppm referred to the proton of the azomethine (H C N) fragment, in conformity with the reported values of δ = 8.72 ppm in earlier investigations by Gelan, 66 confirming the successful formation of the desired ligand. The hydroxyl proton was observed at lowfield shift δ = 13.40 ppm, in agreement with the reported values of δ = 13.36 ppm in earlier investigations by Chang-Jian et al 67 and further compared work 68 that confirmed the strong hydrogen bond between the imino nitrogen and the hydroxyl function on the aromatic ring.…”
Section: Structural Characterizationsupporting
confidence: 86%
See 1 more Smart Citation
“…NMR observations in DMSO-d 6 as solvent: The 1 H-NMR spectrum of un-complexed ligand (H 2 L) noticed highly de-shielded singlet at a low-field region δ = 8.66 ppm referred to the proton of the azomethine (H C N) fragment, in conformity with the reported values of δ = 8.72 ppm in earlier investigations by Gelan, 66 confirming the successful formation of the desired ligand. The hydroxyl proton was observed at lowfield shift δ = 13.40 ppm, in agreement with the reported values of δ = 13.36 ppm in earlier investigations by Chang-Jian et al 67 and further compared work 68 that confirmed the strong hydrogen bond between the imino nitrogen and the hydroxyl function on the aromatic ring.…”
Section: Structural Characterizationsupporting
confidence: 86%
“…63 Hence, it supports the suggested composition of Sn (ph) 2 (HL) 2 complex under discussion. Meanwhile, the 13 C-NMR spectrum of ligand (H 2 L) provides more proof for its successful manufacturing, as prompted by observations of peaks; a lower field 13 C-NMR signals set (δ = 116-162.34, $166.97, and $61-95 ppm) characteristic for the aromatic ring carbons, azomethine and carbon skeleton of D-glucosamine segments, 59,66 respectively, that shifted to (δ = 108-143, $157.04, and $53-93 ppm) upon complexation respectively. The chemical shifts of 1 H and 13 C-NMR are listed and assigned in (Tables 3 and 4) and exhibited in (Figures S4 and S5).…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Chitosan and its nanocomposite derivatives are used in a many field that interested in the life sciences and technology such as biomedical and pharmaceutical applications [29]. Moreover, many studies have shown that the modification of chitosan via Schiff bases condensation to enhance its biological activity [30].…”
mentioning
confidence: 99%